Karakteristik Petis berdasarkan Bahan Baku dan Penambahan Bahan Pangan yang Berbeda: Artikel review - Romadhon, Taufikkilah; Khoirina, Adhian Dini; Alvianto, Dikianur; Rahayu, Lisa Fitri Rahayu; Purba, Nova Solina; Muzdalifah, Nuzlul (Jurnal Ilmiah Pangan Halal, 2025)
The aim of this article is to review the effects of processing methods, raw materials, and food additives on the quality of petis. The method used in this study is a literature review by collecting and analyzing data from relevant national and international journals. The results indicate that thermal processing, particularly temperature and cooking duration, significantly influence the chemical and sensory quality of petis, including protein content, moisture level, taste, aroma, and texture. The choice of raw materials also affects the final product, with shrimp broth producing the highest protein content. Additionally, food additives such as flour serve as thickeners that impact the sensory properties, especially texture. Wheat flour has been reported to provide the best effect in improving both texture and protein levels in petis. Furthermore, the use of sugars—such as palm sugar and liquid sugars—contributes to the characteristic taste and color of petis through caramelization and Maillard reactions. Product innovation, such as the development of instant or powdered petis, is also being explored to extend shelf life and enhance convenience. A proper combination of processing techniques, raw materials, and food additives is essential for producing high-quality petis.